Post-pericardiectomy ECMO for constrictive pericarditis: a case series and literature review - Bin Jia; Shujie Yan; Yong Luo; Jian Cheng; Jie Cheng; Junjie Fei; Yushuang Gao; Xiao Liao; Luyu Bian; Jian Wang; Yuan Teng; Gang Liu; et al. (BMC Anesthesiology)
Abstract Background Pericardiectomy is the curative treatment for constrictive pericarditis, yet postoperative low cardiac output syndrome (LCOS) may occur. The application of venoarterial extracorporeal membrane oxygenation (VA-ECMO) in post-pericardiectomy refractory LCOS has limited case reports, and its effectiveness and safety remain unclear. This study aims to provide evidence for the effectiveness of ECMO in treating post-pericardiectomy refractory LCOS. Methods Nine cases of post-pericardiectomy ECMO from two high-volume pericardiectomy centers in China were retrospectively reviewed. Meanwhile, a literature search was performed in PubMed and Embase on December 4, 2024. After screening, 5 articles were finally included for data extraction and comprehensive analysis. Results Case Series: There were 4 cases of tuberculous etiology, 1 with a history of cardiac surgery, and 4 idiopathic cases. All patients were in New York Heart Association class III - IV at baseline. All the patients undertwent pericardiectomy via median sternotomy, and 5 patients underwent concomitant valve procedures. One patient failed to wean from the cardiopulmonary bypass (CPB) and was transferred to femoral VA-ECMO. Eight patients received femoral VA-ECMO support 4–96 h after surgery due to refractory LCOS. All the patients survived to discharge with good neurological outcomes after 120–192 h of ECMO support. Two patient were lost to follow-up, and the rest 7 patients survived to follow-up with a mean follow-up of 56 months. Literature Review: 4 case reports and 1 retrospective study were identified. In the retrospective study of 69 patients, 8 received ECMO during or after pericardiectomy with a hospital mortality rate of 63%. The four Patients of the 4 case reports were all survival at hospital discharge. Conclusions VA-ECMO might be effective for refractory LCOS after pericardiectomy in patients with constrictive pericarditis, and could improve survival rates.